"Role of CT Coronary Angiography in Recanalization of Chronic Total Occlusion" - Roy, Sanjeeb (Curr Cardiol Rev, 2015)
Chronic total occlusion (CTO) is considered as the most challenging frontier in interventional cardiology and the last one to be conquered. With availability of state of the art hardware, wires and catheters in particular and increased skills of the operators, the success rate for recanalization of CTO by percutaneous catheter intervention (PCI) has improved. Yet the complications rate and longterm adverse events are high, mostly due to failure in tracking or navigation of hardware through the occluded CTO segment, prolonged exposure to radiation and high doses of contrast used. Therefore, proper selection of patient is of utmost importance. One of the major challenges for successful CTO recanalization is satisfactory visualization of the occluded CTO segment. Conventional invasive catheterization fails to fill the gap and the shortcomings and handicaps of such invasive imaging can be resolved with the use of non-invasive CT coronary angiography (CTCA). CTCA helps to better define the morphological features of the occluded CTO segment, which are established predictors of success, like the actual length of the occluded segment and any calcification or tortuosity in its course. Integration of reconstructed three-dimensional CT coronary images with twodimensional fluoroscopic images, offers directional guide to select the best angiographic plane for visualization of angiographically “missing segment”. With advances in CT technology, CTCA has now become an established technology for pre-procedure evaluation of CTO segment, thereby help in planning and execution of successful PCI.